Management of The Kayangan Api Tourist Attraction to Create Superior Tourism: Adaptive Governance Analysis - Enggarudin, Muhammad Maksum; Wulandari, Septi; Kasiami, Sri (Universitas Muhammadiyah Gorontalo, 2025)
This study aims to analyze adaptive governance in managing the Kayangan Api tourist attraction to promote superior tourism in Bojonegoro Regency through collaboration, flexibility, and learning processes. Adaptation is necessary to meet the demands of better tourism management. This research uses a qualitative descriptive method. Primary data sources include interviews and observations, while secondary data come from documentation collected at the research site. The informant selection was done through purposive sampling, based on criteria indicating that informants are knowledgeable about the Kayangan Api tourist attraction. The results show that adaptive governance in managing Kayangan Api includes collaboration between the Department of Culture and Tourism and Perhutani through profit-sharing agreements, flexibility in services—particularly for tour guides—and a learning process where managers evaluate criticism and suggestions. The challenges identified include the need for tour guides to be more responsive, innovative, and for tourism promotion to be optimized.